Persepsi Lingkungan Kerja Psikologis Terhadap Kepuasan Kerja - Moch Hafid; Uswatun Hasanah (Journal An-Nafs: Kajian Penelitian Psikologi, 2016)
This study examines the influence of environmental perceptions Work on job satisfaction at the police members Jombang. The hypothesis is There Influence Perception of Work Environment to satisfaction of Work Psychology at the police members Jombang. The variables in this study perception of the work environment and job satisfaction, subjects in this study were 40 members of the police force in Jombang. Data collection methods be used in this study using a scale measuring perceptions of the work environment and job satisfaction measurement scale in the form of a questionnaire given to research subjects to be filled. Data analysis using Produck Moment, Conclusions of the statistical analysis showed the value of product moment correlation r xy = -0.0327, p = 0.000 (p <0.005), this shows that a very significant positive influence between work environment Psychological Work (X) with Job satisfaction (Y) means the better perception of the psychological work environment, the higher the job satisfaction member of the police work. Thus the hypothesis is accepted